Global solution curves for first order periodic problems, with applications. (December 2020) - Korman, Philip; Schmidt, Dieter S.
Abstract: Using continuation methods and bifurcation theory, we study the exact multiplicity of periodic solutions, and the global solution structure, for periodic problems of first order. The results are applied to a population model with fishing, and to the existence and stability of limit cycles. We also describe in detail our numerical computations of curves of periodic solutions, and of limit cycles.